Oligodon cicadophagus, a new kukri snake from southern peninsular Thailand (Squamata: Colubridae) - Pauwels, Olivier S. G.; Donbundit, Nattasuda; Sumontha, Montri; Meesook, Worawitoo (Zootaxa, 2025)
We describe a new kukri snake, Oligodon cicadophagus sp. nov., from the limestone reliefs of the Phuket Mountain Range in Krabi and Phang-Nga provinces in southern peninsular Thailand. A member of the Oligodon cinereus group, it can be distinguished from all other congeneric species by the combination of its maximal known snout-vent length of 537 mm; 11 maxillary teeth; eight supralabials; one preocular and one presubocular; 17-17-15 dorsal scale rows; 159–168 ventrals, and 50 subcaudals in males; a single anal scale; hemipenes bilobed with large broad lobes, no distinct flounced calyces and unforked sulcus spermaticus; dorsal surface of head, body and tail uniformly olive-gray, without nuchal chevron, dorsal stripes, crossbands, blotches or reticulations; and a venter cream anteriorly turning to dark gray posteriorly.